MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MELALUI MODEL PROJECT BASED LEARNING DI KELAS IV SD TEMA 2 SUBTEMA 1 PEMBELAJARAN 1 DI SDN 060870 KEC. MEDAN TIMUR, T.A. 2022/2023 - Septia Anggraini (Universitas Pahlawan Tuanku Tambusai, 2022)
The background of this research is the low learning outcomes of fourth grade students at SD Negeri 060870, the teacher's skills in learning are still focused on the teacher, and the teacher does not provide opportunities to ask questions to students and does not involve students in the learning process. This type of research is classroom action research carried out in 2 cycles and 4 stages, namely: planning, implementing, observing, and reflecting. The research subjects were 22 grade IV students of SD Negeri 060870. The data collection tools used were learning achievement tests and observation sheets. Based on the results of the research above, it can be interpreted that the results of the initial test (pre-test) of students still experience a level of mastery learning below the average, namely 62.4 with a proportion of classical mastery of 68%. After the first cycle, there was an increase where students who scored ≤70 or did not finish were 9 people (40%) and who got scores ≥ 70% or completed as many as 13 people (59%). This shows that the value of student learning outcomes in cycle I has not yet reached the level of learning success (classical decision) because it is still below 85%. Based on the results of the research on the implementation of cycle II, it can be seen that 18 people (81%) have completed, and 4 people (18%) have not completed. The classical mastery level reaches 92% which indicates that the classical learning outcomes have been completed (≥85%). In the first cycle, teaching teacher activity was in the good category with an average proportion of 70.7%, and in the second cycle, teaching teacher activity increased with an average proportion of 90% in the very good category. In the first cycle, student learning activities were classified as in the less category, with the average proportion of students at 62.50%, while in the second cycle, student learning activities increased with the proportion of 77.6% in the good category. Keywords: Learning Outcomes, Project Based Learning, PPG